Electrochemical noise (EN) technique: review of recent practical applications to corrosion electrochemistry research. Issue 13 (3rd July 2019) - Obot, I. B.; Onyeachu, Ikenna B.; Zeino, Aasem; Umoren, S. A.
Abstract: The ability to analyze different electrochemical corrosion phenomena, in–situ, without requiring any form of electrode perturbation has strongly attracted the attention of corrosion researchers towards the application of electrochemical noise (EN) analysis method. With the ability to analyze stochastic and chaotic electrode potential and current fluctuations at EOCP, the EN analysis method is capable of providing information about the kinetics and mechanism of metallic corrosion with accuracy that can match conventional electrochemical techniques. Herein, we review the recent applications of EN analysis method to electrochemical corrosion research. We discuss briefly the theory behind the measurement of EN, and then highlight some of its application in the evaluation of corrosion inhibitors, pitting corrosion, coatings on metals, microbiologically–induced corrosion, as well as CO2 –corrosion. The drawbacks of the EN analysis method have also been highlighted and future considerations on the use of this important electrochemical technique have also been proposed.